PESANTREN: CANDRADIMUKA NILAI-NILAI KARAKTER SANTRI - Madarik, Muhammad; Puadi, Hairul (Pascasarjana Universitas Al-Qolam Malang, 2024)
Especially in relation to the scientific structure of Islamic boarding schools, knowledge related to Arabic, such as sharaf, nahwu and other tool knowledge, knowledge related to sharia, such as fiqh, both regarding worship (ubudiyah) and transactions (mu'amalat), knowledge that related to the Al-Qur'an along with knowledge about the causes of the revelation of verses (asbab al-nuzul), correlation between verses, verses and hadith, tafsir-tafsir, and others (ulum al-Qur'an), knowledge of hadith along with knowledge about the causes of the existence of hadith (asbab al-wurud), etc. (mustalah al-hadith), knowledge related to logic (ilmu al-mantiq), knowledge related to the purification of the soul (tazkiyah al-nafs) which is framed in knowledge about etiquette (tashawwuf), knowledge that discusses the power and oneness of God (tauhid). The values built by Islamic boarding schools can be categorized into: (1) Essential values including: the value of honesty (al-shidq), the value of spirituality (al-ibadah), the value of struggle (al-jihad), the value of tolerance (al-tasamuh), the value of independence (al-i'timad ala al-nafs), the value of sincerity (al-ikhlas), example (uswah hasanah). (2) Instrumental values which include: wisdom, freedom to be guided, self-government, togetherness (collectivism). So it is not surprising that Islamic boarding schools are considered as an education system that can play an empowerment role in strengthening civil society (mobilization of civil society forces) maximally and effectively. Keywords: Islamic Boarding School, Values, Curriculum, Character